1864-1865 Terr. of N.M. Laws 406-08 - (:unkn) unknown (My University, 1864)
Ch. 61, § 25: It shall be unlawful for any person to carry concealed weapons on their persons, or any class of pistols whatever, bowie knife (cuchillo de cinto), Arkansas toothpick, Spanish dagger, slungshot, or any other deadly weapon, of whatever class or description that may be, no matter by what name they may be known or called, under the penalties and punishment which shall hereinafter be described.
Keywords: CARRY - CONCEALED